Maternal, neonatal, pregnancy outcome characteristics of pregnant women with high plasma cell-free DNA concentration in non-invasive prenatal screening: a retrospective analysis - Xing, Lingling; Bai, Ting; Liu, Sha; Liu, Jianlong; Jing, Xiaosha; Deng, Cechuan; Xia, Tianyu; Liu, Yunyun; Cheng, Jing; Wei, Xiang; Luo, Yuan; Zhou, Quanfang; et al. (Frontiers in Pediatrics, 2023)
Objective: Cell-free DNA (cfDNA) is a useful biomarker in various clinical contexts. Herein, we aimed to identify maternal characteristics and pregnancy outcomes associated with a failed NIPS test due to high cfDNA concentrations..A retrospective study of cases with high plasma cfDNA concentration in pregnant women in which NIPS test was performed (from 174,318 cases). We reported the detection of 126 cases (118 with complete clinical information) in which the high amount of cfDNA did not allow the performance of NIPS and study the possible causes of this result.Results: 622(0.35%) of 174,318 pregnant women had failed the NIPS test, including 126(20.3%) cases with high plasma cfDNA concentrations. The failed NIPS due to high plasma cfDNA concentrations was associated with maternal diseases and treatment with low-molecular-weight heparin (LMWH). Further follow-up of the 118 pregnant women in the case group revealed that the This is a provisional file, not the final typeset article pregnancy outcomes included 31 premature deliveries, 21 abortions. The cfDNA concentrations of pregnant women with preterm deliveries were 1.15(0.89,1.84), which differed significantly from those who had full-term deliveries.Conclusions: Among pregnant women with high cfDNA concentrations, systemic autoimmune diseases, pregnancy complications and LMWH were associated with increased incidence of failed NIPS test. High maternal cfDNA concentrations may not be associated with chromosomal abnormalities in the fetus. However, they should be alerted to the possibility of preterm births and stillbirths. Further clinical studies on pregnant women with high cfDNA concentrations are required.